ANALISIS REGULASI PENEGAKAN HUKUM HAK ASASI MANUSIA (HAM) DI INDONESIA - Arifin, Mochammad (Universitas Nahdlatul Ulama Blitar, 2023)
This article discusses law enforcement regarding human rights in Indonesia based on law positive in Indonesia. The author chose this title because until now law enforcement in particular related to human rights in Indonesia is still not optimal. Main problem in this article are: how the law is applied to violations of human rights, which institutions prosecute human rights violators, means of settlement used in cases of violations of human rights in Indonesia. The conclusion of the problems discussed is the application of law to violations of human rights in Indonesia is guided by law no. 26 years 2000 concerning the Human Rights Court, where in the Act is mentioned about ad hoc human rights courts, which do not different from ordinary courts, especially criminal courts. Ketwords: Law Enforcement, Human Right